Chest X-Ray Findings and Severity Score of Patients with Respiratory Symptoms in COVID-19 Intensive Care Unit of a Teaching Hospital - Sharma, Umesh Kumar; Thapaliya, Suraj; Shrestha, Manmohan Bir; Shrestha, Raju; Thakur, Laxman; Rai, Ujwal; Singh, Jitendra Kumar (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Chest X-rays are important for tracking the progression of lung abnormalities, particularly in critically ill COVID-19 patients in the intensive care units (ICU). We aimed to assess correlation of chest X-ray findings with the COVID-19 disease severity and outcome. Methods: This prospective observational study was conducted at B & C Teaching Hospital, Birtamode from 15 March to 15 July 2021. All diagnosed COVID-19 patients admitted in the ICU for respiratory distress with oxygen saturation < 90% and evaluated by portable X-rays were enrolled. The radiographic findings were evaluated for the distribution and patterns of affection, and the total severity score was calculated using RALE scales of 0 - 8 and Brixia scales of 0 - 18. The scores were then compared between the expired and improved patients. Results: The age of patients (mean ± SD) was 48.2 ± 13.84 years. During the first four days of hospitalization, there was no significant difference in Brixia score (p = 0.793) or RALE score (p = 0.842) between expired and improved patients.The differences in both (Brixia and RALE) scores grew with each passing day (p < 0.05). The Brixia and RALE severity scores had a strong positive correlation at various stages of disease in both expired and improved patients. (r > 0.75, p < 0.001). Conclusion: In resource limited setting, the severity scores (RALE or Brixia) can be used as a quantitative method of the extent of COVID-19 pneumonia, correlating with an increased risk of ICU admission.